Systematic review: Safety of balloon assisted enteroscopy in Crohn’s disease - Arulanandan, Ahilan (World J Gastroenterol, 2016)
AIM: To determine the overall and comparative risk of procedure related perforation of balloon assisted enteroscopy (BAE) in Crohn’s disease (CD). METHODS: Systematic review (PROSPERO #CRD42015016381) of studies reporting on CD patients undergoing BAE. Seventy-three studies reporting on 1812 patients undergoing 2340 BAEs were included. Primary outcome of interest was the overall and comparative risk of procedure related perforation of diagnostic BAE in CD. Secondary outcomes of interest were risk of procedure related perforation of diagnostic double balloon enteroscopy (DBE), risk of procedure related perforation of therapeutic BAE, efficacy of stricture dilation, and clinical utility of endoscopically assessing small bowel disease activity. RESULTS: Per procedure perforation rate of diagnostic BAE in CD was 0.15% (95%CI: 0.05-0.45), which was similar to diagnostic BAE for all indications (0.11%; IRR = 1.41, 95%CI: 0.28-4.50). Per procedure perforation rate of diagnostic DBE in CD was 0.12% (95%CI: 0.03-0.44), which was similar to diagnostic DBE for all indications (0.22%; IRR = 0.54, 95%CI: 0.06-0.24). Per procedure perforation rate of therapeutic BAE in CD was 1.74% (95%CI: 0.85-3.55). Eighty-six percent of therapeutic perforations were secondary to stricture dilation. Dilation was attempted in 207 patients and 30% required surgery during median follow-up of 18 months. When diagnostic BAE assessed small bowel disease activity, changes in medical therapy resulted in endoscopic improvement in 77% of patients. CONCLUSION: Diagnostic BAE in CD has a similar rate of perforation as diagnostic BAE for all indications and can be safely performed in assessment of mucosal healing.